Evaluación del efecto de los antidegradantes no manchantes derivados de cera parafínicas y fenoles en las propiedades mecánicas de la suela de caucho, en Croydon Colombia S.A. (2017)
The purpose of this research is to evaluate and analyze four non-staining antidegradants derived from paraffin waxes and phenols, in the mechanical properties of rubber sole of footwear manufactured by Croydon Colombia S.A. Initially, it's identified raw materials, machines and methodologies used during the process of making the rubber soles. Subsequently, a pre-experimentation is developed in order to understand the behavior of each antidegradant at different dosages with respect to the abrasion and flexion properties, identifying those with higher values in the last mechanicals testing. Based on the results of the pre-experimentation, a 2ˆ4 factorial experimental design is developed with a replicate. It is concluded that the antidegradant D in the concentration of 1phr is the only one that meets all the requirements of the NTMD-0090-A4 in terms of mechanical properties. Finally, a cost estimate is made for the current formulation used by the company and the one proposed in this work for the elaboration of the rubber soles of the tennis boot.